Catalytic articles for engine exhaust treatment

By introducing micron- and nano-scale interparticle pores in the catalyst coating of TWC catalytic products, the problem of insufficient diffusion of exhaust gas in the catalyst coating is solved, and the catalytic performance is significantly improved.

CN119907714APending Publication Date: 2025-04-29BASF MOBILE EMISSION CATALYST GMBH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380048248.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-07-04
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult for existing TWC catalytic products to fully diffuse exhaust gas to the depth of the catalyst coating at high aerial speeds, resulting in poor catalytic performance.

Method used

A catalytic article containing a PGM-based catalyst coating with interparticle pores of micron and nanoscale on the substrate, in the logarithmic differential pore volume distribution determined by the mercury insulator poreness determination, peaks of pore volume diameters of nano- and micron-scale are in the range of 90.0 nm to 140.0 nm and 5.5 μm to 10.0 μm, respectively.

Benefits of technology

Improves gas diffusion, promotes the interaction between the feed gas and the active site, and enhances the performance of exhaust gas purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197176800000201
    Figure BDA0005197176800000201
  • Figure BDA0005197176800000211
    Figure BDA0005197176800000211
  • Figure BDA0005197176800000212
    Figure BDA0005197176800000212
Patent Text Reader

Abstract

A catalytic article comprising a catalyst coating on a substrate wherein the catalyst coating comprises at least one catalyst coating comprising a platinum group metal component in a supported form and having such a pore volume distribution that the platinum group metal component is in a supported form, the present invention is characterized in that the peak top of the pore volume diameter at the nanoscale is present in the range of 90.0 nm to 140.0 nm and the peak top of the pore volume diameter at the micron size is present in the range of 5.5 [mu] m to 10.0 [mu] m in a logarithmic differential pore volume distribution as determined by mercury intrusion porosity assay. The invention also relates to a method for preparing the catalytic article and an exhaust gas treatment system comprising the catalytic article.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a three-way conversion catalytic article that can be used to treat engine exhaust and an exhaust treatment system containing the catalytic article. In particular, the present invention relates to a catalytic article that can be used to treat exhaust from a stoichiometric engine, especially a saddle-type vehicle engine. Background Art

[0002] The engine exhaust gas basically includes particulate matter and gaseous pollutants, such as unburned hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NOx). For stoichiometric engines, such as gasoline engines, operating near the optimal air / fuel ratio, a three-way conversion catalyst (hereinafter interchangeably referred to as a TWC catalyst or TWC) is generally used to simultaneously oxidize unburned hydrocarbons and carbon monoxide and reduce nitrogen oxides. It is known that the TWC catalyst is effective under near stoichiometric conditions, under which the basic reactions including reduction and oxidation can be exemplified as follows:

[0003] 2NO+2CO→N2+2CO2

[0004] 2CO+O2→2CO2

[0005] 2C2H6+7O2→4CO2+6H2O.

[0006] TWC catalysts typically utilize one or more platinum group metals (PGMs), such as rhodium (Rh), platinum (Pt), palladium (Pd), ruthenium (Ru), osmium (Os) and iridium (Ir) as catalytically active species, which are typically supported on carrier particles of refractory metal oxides and / or oxygen storage capacity (OSC) materials. The carrier particles carrying the PGMs are typically coated on a ceramic or metal honeycomb substrate to provide a TWC catalytic article. The TWC catalytic article may have a single coating or multiple different coatings of the TWC catalyst.

[0007] As one of the TWC catalytic products used in various vehicles, the TWC catalytic product used for saddle-type vehicles is particularly required to exert a high purification ability, because such catalytic products have a small volume capacity due to the limited space for installing the catalytic products, are subject to rapid atmospheric changes, and are easily exposed to high temperatures. When the TWC catalytic product has a single thick coating or multiple coatings, it is difficult for the exhaust gas to diffuse into the inner part of the catalyst coating close to the substrate side. In addition, when the TWC catalytic product is used at a high space velocity, it is difficult for the exhaust gas to diffuse into the deep part of the catalyst coating, and therefore the performance of the catalyst cannot be fully manifested. In order to solve the problem of insufficient diffusion of such exhaust gas in the catalyst coating, some special catalyst compositions, configurations or structures for TWC catalytic products have been proposed.

[0008] For example, WO2015 / 037613A discloses an exhaust gas purification catalyst comprising a catalyst layer, the catalyst layer comprising two or more types of inorganic porous particles each having a different particle size, a catalytically active component and voids, wherein as a first characteristic, the condition L / 2 / (πS) is satisfied. 1 / 2 The voids of ≧2 account for 50% or more of the number of all voids in the catalyst layer, where S represents the void cross-sectional area and L represents the void cross-sectional perimeter; and as a second characteristic, in the void cross-sectional area in the catalyst layer, the average void radius determined assuming that the void shape is a perfect circle is 10 μm to 20 μm. It is described that the miscibility and diffusivity of the gas in the catalyst layer are improved, and thus excellent purification performance can be exhibited.

[0009] US2017 / 0232425A1 discloses an exhaust gas purification catalyst, which has a first catalyst layer formed on a substrate surface and a second catalyst layer formed on an upper side of the first catalyst layer, wherein the first catalyst layer contains a precious metal, an OSC material and aluminum oxide, and the mass ratio of the OSC material to the aluminum oxide contained therein is in the range of 1:7 to 1:3, and the second catalyst layer contains a precious metal, an OSC material and aluminum oxide, and the mass ratio of the OSC material to the aluminum oxide contained therein is in the range of 1:1 to 10:0, and wherein the average particle size (D 50 ) is 10 μm to 16 μm, and the average particle size (D 50 ) is 3 μm to 12 μm. It is described that the gas diffusivity in the catalyst layer can be improved, the catalytic activity is rarely reduced, and the entire catalyst layer can be effectively used even in an internal combustion engine that is exposed to high-temperature exhaust gas and is used in an exhaust atmosphere with an extremely high space velocity of the exhaust gas passing therethrough.

[0010] WO2013118425A1 discloses a porous apatite catalyst layer containing apatite, wherein in the logarithmic differential void volume distribution measured by mercury intrusion porosimetry, the peak top exists in the void volume diameter range of 100nm to 1000nm. It is described that a new catalyst structure is provided, which can maintain gas diffusivity deep into the catalyst layer even under conditions of high gas flow rate.

[0011] WO2014156676A1 discloses a catalyst structure, which includes a substrate, an upper catalyst layer and a lower catalyst layer, and in the logarithmic differential pore volume distribution analyzed by mercury intrusion porosimetry, the catalyst structure has a first peak or a second peak at a pore volume diameter of 10nm to 50nm and a pore volume diameter of 50nm to 100nm, respectively. It is described that the catalyst structure can increase gas diffusivity deep into the catalyst layer and can fully demonstrate the function as a three-way catalyst.

[0012] There is still a need to provide a TWC catalytic article that can improve gas diffusion deep into the catalyst, promote the interaction between the feed gas and the active sites, and enhance the performance of exhaust gas purification. Summary of the invention

[0013] The object of the present invention is to provide a catalytic article, especially a catalytic article for a saddle-type vehicle, which has a high performance in reducing HC, CO and NO compared to conventional TWC catalysts for saddle-type vehicles. x The overall catalytic performance is improved.

[0014] It has surprisingly been found that the objects of the present invention are achieved by a catalytic article comprising a PGM-based catalyst coating having inter-particle pores on the micrometer and nanometer scale on a substrate.

[0015] Therefore, in a first aspect, the present invention provides a catalytic article, especially a TWC catalytic article, which comprises a catalyst coating on a substrate, wherein the catalyst coating comprises at least one catalyst coating, the at least one catalyst coating comprising a platinum group metal component in a supported form and having a pore volume distribution such that in the logarithmic differential pore volume distribution as determined by mercury intrusion porosimetry, the peak top of the nanometer-scale pore volume diameter exists in the range of 90.0 nm to 140.0 nm, and the peak top of the micrometer-scale pore volume diameter exists in the range of 5.5 μm to 10.0 μm.

[0016] In a second aspect, the present invention provides a method for preparing the catalytic product described in the first aspect, the method comprising

[0017] - applying a slurry comprising a platinum group metal component in supported form and a pore former to a substrate, and optionally drying, and

[0018] - calcination to form a catalyst coating,

[0019] Wherein the pore former is in the form of particles, and based on the loading of the catalyst coating as formed, the pore former is used in an amount of at least 0.5 wt%.

[0020] In a third aspect, the present invention provides an exhaust gas treatment system comprising a catalytic article as described herein, the catalytic article being located downstream of a stoichiometric engine, particularly a saddle-type vehicle engine.

[0021] In a fourth aspect, the present invention provides a method for treating an exhaust gas flow from a stoichiometric engine, the method comprising contacting the exhaust gas flow with a catalytic article or exhaust gas treatment system as described herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1A and Figure 1B The logarithmic differential pore volume distributions of samples S1 to S4 as described in the Examples are shown.

[0023] Figure 2A and Figure 2B The logarithmic differential pore volume distributions of samples S5 to S8 as described in the Examples are shown. DETAILED DESCRIPTION

[0024] The present invention is described in detail below. It should be understood that the present invention can be embodied in many different ways and should not be construed as being limited to the embodiments set forth herein.

[0025] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. The terms "comprising," "including," and the like are used interchangeably with "containing," and are to be interpreted in a non-limiting, open-ended manner. That is, for example, additional components or elements may be present. The expression "consisting of" or cognates may be encompassed by "comprising" or cognates.

[0026] As used herein, the terms "platinum group metal component," "palladium component," "platinum component," and "rhodium component" are intended to describe the corresponding platinum group metal in any possible valence state, which may be, for example, the metal or metal oxide in a catalytically active form, or may be, for example, a metal compound, complex, etc. that decomposes or is otherwise converted to a catalytically active form upon calcination or use of the catalyst.

[0027] As used herein, the term "support" refers to a material in particulate form for receiving and supporting one or more platinum group metal (PGM) components and optionally one or more other components, such as stabilizers, promoters and binders.

[0028]

[0026] Any reference herein to a platinum group metal component being in "supported form" is intended to mean that the platinum group metal component is supported on and / or in support particles.

[0029] In this paper, the 3” or “g / in 3 Any reference to loading in units of "is intended to mean the weight of a particular component or coating per unit volume of the substrate or substrate portion on which it is supported.

[0030] As used herein, the term "catalyst coating" refers to a catalyst-containing covering deposited on the surface of a substrate wall that defines a channel through which the exhaust gas flow passes. The catalyst coating may have a non-layered configuration or a layered configuration. For a non-layered configuration, the catalyst coating consists of a single coating; for a layered configuration, the catalyst coating consists of two or more coatings, at least one of which is a catalyst-containing coating. It should be understood that the coating can be prepared by repeating the coating step two or more times to obtain a target loading, and will therefore include more than one sublayer having the same chemical composition and catalytic activity, which can be distinguished only by SEM analysis. Such coatings containing more than one sublayer having the same chemical composition and catalytic activity will be referred to as a single coating or a coating. Therefore, when two or more coatings are mentioned herein, the coatings will have different chemical compositions or catalytic activities from each other.

[0031] As used herein, the term "catalyst coating" refers in particular to a coating comprising a platinum group metal component in supported form.

[0032] In this document, any reference to a coating "on a substrate" is intended to mean that the coating is carried by the substrate, which may be blank or already carry one or more other coatings. In addition, any reference to applying a slurry "on a substrate" is intended to mean that the slurry is applied to a substrate, which may be blank or already carry one or more coatings.

[0033] As used herein, the term "solid content" is intended to refer to the content of matter that is not volatile under calcination conditions, expressed as a weight ratio measured before and after the calcination process (eg, at 500°C for 1 hour).

[0034] As used herein, the terms "exhaust gas," "exhaust gas flow," and the like may be used interchangeably with one another and refer to any engine effluent that may also contain particulate matter.

[0035] According to a first aspect of the present invention, a catalytic article is provided, which comprises a catalyst coating on a substrate, wherein the catalyst coating comprises at least one catalyst coating, the at least one catalyst coating comprising a platinum group metal component in a supported form and having a pore volume distribution such that in the logarithmic differential pore volume distribution as determined by mercury intrusion porosimetry, the peak top of the nanometer-scale pore volume diameter exists in the range of 90.0 nm to 140.0 nm, and the peak top of the micrometer-scale pore volume diameter exists in the range of 5.5 μm to 10.0 μm.

[0036] It should be understood that the catalytic article according to the present invention may comprise a catalyst coating consisting of two or more coatings on a substrate, wherein at least one coating comprises a platinum group metal component in a supported form, which is also referred to as a catalyst coating. When the catalyst coating of the catalytic article according to the present invention consists of two or more coatings, it is preferred that at least the outermost coating has a pore volume distribution as described herein on the substrate from the perspective of increasing gas diffusivity toward the inner layer.

[0037] In some embodiments, the catalyst coating of the catalytic article according to the present invention may comprise or consist of one catalyst coating comprising a platinum group metal component in supported form.

[0038] In some other embodiments, the catalyst coating of the catalytic article according to the present invention may comprise or consist of two catalyst coatings, the two catalyst coatings comprising the platinum group metal component in supported form. For example, the catalyst coating of the catalytic article according to the present invention consists of a top catalyst coating comprising the first platinum group metal component in supported form and a bottom coating comprising the second platinum group metal component in supported form.

[0039] In some further embodiments, the catalyst coating of the catalytic article according to the present invention may comprise three or more coating layers, wherein at least one, preferably two or more, of the coating layers comprises a platinum group metal component in supported form.

[0040] In any of the above embodiments, in the logarithmic differential pore volume distribution as measured by mercury intrusion porosimetry, the peak top of the nanometer-scale pore volume diameter in the pore volume distribution preferably exists in the range of 100.0 nm to 130.0 nm, or 110.0 nm to 120.0 nm. Additionally or alternatively, in the logarithmic differential pore volume distribution as measured by mercury intrusion porosimetry, the peak top of the micrometer-scale pore volume diameter in the pore volume distribution exists in the range of 6.0 μm to 8.0 μm, or 6.0 μm to 7.5 μm.

[0041] In the catalyst coating of the catalytic article according to the present invention, the peak of the nanoscale pore volume diameter extends from 10 nm to 250 nm, and the peak of the microscale pore volume diameter extends from 1 μm to 22 μm in the logarithmic differential pore volume distribution as determined by mercury intrusion porosimetry.

[0042] In addition, for the peak value of the nanoscale pore volume diameter as described herein, the cumulative pore volume is preferably at least 0.05 ml / g, or at least 0.09 ml / g, such as in the range of 0.05 ml / g to 0.50 ml / g, or 0.08 ml / g to 0.30 ml / g, or 0.09 ml / g to 0.18 ml / g. For the peak value of the microscale pore volume diameter as described herein, the cumulative pore volume is preferably at least 0.01 ml / g, or at least 0.02 ml / g, in particular, at least 0.03 ml / g, such as in the range of 0.01 ml / g to 0.10 ml / g, or 0.02 ml / g to 0.06 ml / g, or 0.03 ml / g to 0.06 ml / g.

[0043] It should be understood that the peak values ​​of the nanoscale and microscale pore volume diameters are the peak values ​​of the pores originating from the catalyst coating. Any peak values ​​originating from the substrate pores will not appear in such numerical ranges of the pore volume diameters and will not be calculated when discussing pore distribution or pore volume distribution herein.

[0044] There is no particular limitation on the platinum group metal (PGM) component that can be used for any catalyst coating included in the catalytic article. Typically, the PGM component can be a rhodium (Rh) component, a platinum (Pt) component, a palladium (Pd) component, a ruthenium (Ru) component, an osmium (Os) component, an iridium (Ir) component, or any combination thereof, wherein a Pt component, a Pd component, a Rh component, or any combination thereof is typically used.

[0045] In particular, the catalyst coating of the catalytic article according to the present invention comprises a PGM component selected from a Rh component combined with either or both of a Pt component and a Pd component. The platinum group metal (PGM) component may be contained in the same catalyst coating of the catalytic article. Alternatively, when the catalyst coating of the catalytic article comprises two or more catalyst coatings (the two or more catalyst coatings comprising a PGM component in a supported form), the PGM component may be arranged in different catalyst coatings.

[0046] For example, in some embodiments, the catalyst coating of the catalytic article comprises two catalyst coatings, the two catalyst coatings comprising PGM components in supported form, wherein one catalyst coating comprises a Rh component in supported form and, optionally, a Pt component in supported form as the PGM component, and the other catalyst coating comprises a Pt component in supported form and, optionally, a Pd component in supported form as the PGM component.

[0047] In some specific embodiments, the catalyst coating of the catalytic article comprises or consists of a top catalyst coating and a bottom catalyst coating, wherein the top catalyst coating comprises a PGM component in a supported form, and the bottom catalyst coating comprises a PGM component in a supported form, wherein the top catalyst coating comprises a Rh component in a supported form and optionally a Pt component in a supported form as the PGM component, and the bottom catalyst coating comprises a Pt component in a supported form and optionally a Pd component in a supported form as the PGM component.

[0048] In particular, the catalyst coating of the catalytic article may comprise a top catalyst coating and a bottom catalyst coating, wherein the top catalyst coating comprises a PGM component in a supported form, and the bottom catalyst coating comprises a PGM component in a supported form, wherein the top catalyst coating comprises a Rh component in a supported form as the PGM component, and the bottom catalyst coating comprises a Pt component in a supported form as the PGM component.

[0049] Alternatively, the catalyst coating of the catalytic article may comprise a top catalyst coating comprising a PGM component in a supported form and a bottom catalyst coating comprising a PGM component in a supported form, wherein the top catalyst coating comprises a Rh component in a supported form and a Pt component in a supported form as PGM components, and the bottom catalyst coating comprises a Pt component in a supported form and a Pd component in a supported form as PGM components.

[0050] As useful support materials for the platinum group metal component in the catalytic article according to the present invention, there may be mentioned refractory metal oxides, oxygen storage components, and any combination thereof.

[0051] Refractory metal oxides, which are widely used as support materials for platinum group metal components in catalytic articles for exhaust gas treatment, are generally high surface area alumina-based materials, zirconia-based materials, or combinations thereof. In the context of the present invention, "alumina-based materials" refers to materials comprising alumina as a matrix and an optional dopant. Similarly, "zirconia-based materials" refers to materials comprising zirconium oxide as a matrix and an optional dopant.

[0052] Suitable examples of alumina-based materials include, but are not limited to, alumina, such as a mixture of gamma and delta phases of alumina which may also contain significant amounts of η, κ and θ alumina phases, lanthanum oxide doped alumina, barium oxide doped alumina, ceria doped alumina, zirconia doped alumina, ceria-zirconia doped alumina, lanthanum oxide-zirconia doped alumina, barium oxide-lanthanum oxide doped alumina, barium oxide-ceria doped alumina, barium oxide-zirconia doped alumina, barium oxide-lanthanum oxide-neodymia doped alumina, lanthanum oxide-ceria doped alumina, and any combination thereof.

[0053] Suitable examples of zirconia-based materials include, but are not limited to, zirconia, lanthanum oxide doped zirconia, yttria doped zirconia, neodymia doped zirconia, praseodymia doped zirconia, titania doped zirconia, titania-lanthanum oxide doped zirconia, lanthanum oxide-yttria doped zirconia, and any combination thereof.

[0054] In particular, the refractory metal oxide useful as a support may be selected from barium oxide doped alumina, lanthanum oxide doped alumina, ceria doped alumina, zirconia doped alumina, lanthanum oxide-zirconia doped alumina, lanthanum oxide doped zirconia, and any combination thereof.

[0055] Typically, if used, the refractory metal oxide is present in an amount of 10 to 90 weight percent based on the total weight of the single coating.

[0056] An oxygen storage component (OSC) refers to an entity that has multiple valence states and can react actively with an oxidant such as oxygen or nitrogen oxides under oxidizing conditions, or with a reducing agent such as carbon monoxide or hydrogen under reducing conditions. Typically, the oxygen storage component comprises one or more reducible rare earth metal oxides, such as ceria. The oxygen storage component may also comprise one or more of lanthanum oxide, praseodymium oxide, neodymium oxide, europium oxide, samarium oxide, ytterbium oxide, yttrium oxide, zirconium oxide, and hafnium oxide to form a composite oxide with ceria. Preferably, the oxygen storage component is selected from ceria-zirconia composite oxides and stabilized ceria-zirconia composite oxides.

[0057] Typically, the oxygen storage component, if used, is present in an amount of 15 wt % to 85 wt %, based on the total weight of the single coating.

[0058] The support materials for different platinum group metal (PGM) components in the same catalyst coating may be the same or different. In addition, if the catalytic article according to the present invention comprises two or more catalyst coatings, the support materials for the same platinum group metal (PGM) components in different catalyst coatings may be the same or different. In addition, for the same platinum group metal (PGM) component in one catalyst coating, more than one support may be used.

[0059] The catalytic article according to the present invention may comprise a catalyst coating comprising a platinum group metal component in a supported form in an amount of 0.1 g / in 3 Up to 15.0g / in 3 , or 0.5g / in 3 Up to 10.0g / in 3 , or 1.0g / in 3 Up to 4.0g / in 3 When the catalyst coating of the catalytic article comprises two or more catalyst coatings (the two or more catalyst coatings comprising a platinum group metal component in supported form), the loading amount as described herein refers to the sum of all such catalyst coatings.

[0060] The catalyst coating comprising a platinum group metal component in supported form as described herein may comprise a total loading of 0.5 g / ft 3 Up to 100.0g / ft 3 , or 1.0g / ft 3 Up to 60.0g / ft 3 , or 5.0g / ft 3 Up to 20.0g / ft 3 PGM components within the range of (calculated as corresponding PGM elements).

[0061] The catalyst coating may optionally contain stabilizers and / or promoters as desired. Suitable stabilizers include non-reducible oxides of metals selected from barium, calcium, magnesium, strontium and any combination thereof. Preferably, one or more of barium oxide and magnesium oxide are used as stabilizers. Suitable promoters include non-reducible oxides of rare earth metals selected from lanthanum, praseodymium, yttrium, cerium, tungsten, neodymium, gadolinium, samarium, hafnium and any mixture thereof.

[0062] The catalyst coating having a pore volume distribution as described herein may extend along the entire length of the substrate wall, or along only a portion of the length of the porous wall of the substrate.

[0063] The catalyst coating may be carried on the substrate in the form of a "washcoat". The term "washcoat" has its ordinary meaning in the art and refers to a thin, adherent coating of a catalytic or other material applied to a substrate. Typically, the washcoat is formed by preparing a slurry of particles having a certain solids content (e.g., 15% to 60% by weight) in a liquid medium, which is then applied to the substrate, dried, and calcined to provide a washcoat layer.

[0064] As used herein, a substrate refers to a structure suitable for withstanding the conditions encountered in the exhaust stream from an internal combustion engine, on which is carried a catalyst composition, typically in the form of a washcoat. The substrate is typically made of a refractory material, such as a ceramic or metallic material.

[0065] The metal materials used to construct the substrate may include heat-resistant metals and metal alloys, such as titanium and stainless steel, and other alloys in which iron is a substantial or major component. Such alloys may contain one or more nickel, chromium and / or aluminum, and the total amount of such metals may advantageously account for at least 15% by weight of the alloy, such as 10% to 25% by weight of chromium, 3% to 8% by weight of aluminum, and up to 20% by weight of nickel. The alloy may also contain a small amount or trace amount of one or more metals, such as manganese, copper, vanadium, titanium, etc. The surface of the metal substrate may be oxidized at a high temperature (e.g., 1000° C. or higher) to form an oxide layer on the substrate surface, thereby improving the corrosion resistance of the alloy and promoting adhesion of the repair substrate coating to the metal surface.

[0066] Ceramic materials that can be used to construct the substrate can include any suitable refractory material, for example, cordierite, mullite, cordierite-alumina, silicon nitride, zirconium mullite, spodumene, alumina-silica-magnesia, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, and aluminosilicates.

[0067] In the context of the present invention, a flow-through substrate having a plurality of thin parallel gas flow channels extending from an inlet face to an outlet face of the substrate is preferred, such that the channels are open to a fluid flowing therethrough. A channel having a substantially straight path from its fluid inlet to its fluid outlet is defined by walls to which a catalytic material is applied as a patch coating so that the gas flowing through the channel contacts the catalytic material. The flow channels of the monolithic substrate are thin-walled channels which may have any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal (S-shaped), hexagonal, elliptical, circular, and the like. Such structures may contain 60 to 900 or even more gas inlet openings (i.e., holes) per square inch of cross-section. For example, the substrate may have 200 holes per square inch to 750 holes per square inch, more typically 300 holes per square inch to 600 holes per square inch ("cpsi"). The wall thickness of the flow-through substrate may vary, typically in the range of 1 mil to 0.1 inch.

[0068] It is also possible that the substrate is a wall-flow substrate having a plurality of thin parallel gas flow channels extending from the inlet face of the substrate to the outlet face, wherein alternating channels are blocked at opposite ends. This configuration requires the gas stream to flow through the porous walls of the wall-flow substrate to reach the outlet face. The wall-flow substrate may contain up to 700 pores per square inch (cpsi), for example 100 cpsi to 400 cpsi. The cross-sectional shape of the channel may vary as described above for the channel of the flow-through substrate. The wall thickness of the wall-flow substrate may vary, typically in the range of 2 mils to 0.1 inches.

[0069] The catalytic article according to the present invention can be prepared by conventional washcoating methods. Washcoating methods generally involve applying one or more slurries containing the corresponding catalyst to a substrate. For the purposes of the present invention, a pore former is used in the one or more slurries to provide interparticle pores having a pore volume distribution as described in the first aspect of the present invention. The pore former is contained in the slurry from which the catalyst coating is to be obtained.

[0070] Therefore, in a second aspect, the present invention provides a method for preparing a catalytic product as described in the first aspect, the method comprising

[0071] - applying a slurry comprising a platinum group metal component in supported form and a pore former to a substrate, and optionally drying, and

[0072] - calcination to form a catalyst coating,

[0073] Wherein the pore former is in the form of particles, and based on the loading amount of the catalyst coating as formed, the pore former is used in an amount of at least 0.5 wt%.

[0074] As described herein above, the substrate on which the slurry comprising the platinum group metal component in supported form and the pore former may be a blank substrate, or may have been pre-coated with any suitable base coating. A blank substrate is intended to mean a substrate that does not bear a coating prior to applying the slurry comprising the platinum group metal component in supported form and the pore former thereto.

[0075] The catalyst coating as formed according to the method of the present invention may constitute the catalyst coating of a catalytic article.

[0076] Alternatively, the catalyst coating as formed according to the method of the present invention may constitute one of the coatings of the catalyst coating of the catalytic article. In this case, the catalyst coating as formed may be a top coating or a bottom coating.

[0077] In some embodiments, the present invention provides a method for preparing a catalytic product as described in the first aspect, the method comprising

[0078] - applying a slurry comprising a first platinum group metal component in supported form and a pore former to a substrate, and drying and / or calcining to form a first catalyst coating, and

[0079] - applying a slurry comprising a second platinum group metal component in supported form and a pore former to the first catalyst coating, and optionally drying, and calcining to form a second catalyst coating,

[0080] Wherein the pore former is in the form of particles, and based on the loading amount of each catalyst coating as formed, the pore former is used in an amount of at least 0.5 wt %.

[0081] By such a method, a catalyst coating comprising two catalyst coatings and having a pore volume distribution as specified above can be provided on the substrate. A catalyst coating comprising more catalyst coatings and having a pore volume distribution as specified above can also be provided on the substrate by applying a further slurry comprising a platinum group metal component in supported form and a pore former in an amount as specified above.

[0082] The pore former is preferably used in an amount of at least 1 wt %, or at least 3 wt %, or at least 4 wt %, based on the loading of each catalyst coating layer as formed by the slurry containing the pore former. More preferably, the pore former may be used in an amount of 50 wt % or less, or 30 wt % or less, based on the loading of each catalyst coating layer.

[0083] The pore former can be an organic or inorganic material body that can be burned off during the calcination step and leave voids, thereby providing a coating. For example, the pore former can be selected from organic materials such as natural and synthetic polymers, organic small molecule compounds, inorganic materials such as inorganic salts and carbon materials, natural materials containing cellulose, and any combination thereof.

[0084] Suitable natural and synthetic polymers as pore formers may include, but are not limited to, polyether polyols, such as polyethylene glycol and its alkyl-terminated derivatives, styrene homopolymers or copolymers, such as polystyrene, poly(meth)acrylic acids and their ester derivatives, such as polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, and any combination thereof.

[0085] Suitable organic small molecule compounds as pore formers may include, but are not limited to, benzoic acid and its derivatives, carbamate (urea), sugar crystals, and any combination thereof.

[0086] Suitable inorganic salts as pore formers may include, but are not limited to, ammonium bicarbonate, magnesium carbonate, and any combination thereof.

[0087] Suitable carbon materials as pore formers may include, but are not limited to, carbon black, carbon fibers, graphite, and any combination thereof.

[0088] Suitable cellulose-containing natural materials as pore formers can be granular products from dry plants, including but not limited to sunflower, cotton, rice, wheat, sorghum, breadfruit, sugar cane, corn, bamboo, and any combination thereof. Granular products can be obtained from various parts of plants, such as leaves, bark, straw, roots, husks, and any combination thereof.

[0089] The pore former may be particles having various geometric shapes, including but not limited to spherical, plate-like, cylindrical or fibrous shapes. Preferably, the pore former has an average particle size D in the range of 1 μm to 50 μm, or 10 μm to 30 μm, or 15 μm to 20 μm. 50 Additionally or alternatively, the pore former is in the form of particles having a maximum particle size of 60 μm, preferably 40 μm.

[0090] The steps of preparing and applying the slurry, drying and calcining the coated slurry can be carried out in a conventional manner without any particular restrictions. Generally, the slurry for repairing the substrate coating can be prepared by suspending the subdivided catalyst particles (e.g., PGM components in a supported form) in a suitable excipient (e.g., water), wherein a promoter, a binder, a stabilizer, a viscosity modifier and / or a surfactant can be added. The slurry can be crushed / ground so that substantially all solids have an average particle size greater than 10 microns, for example, in the range of 15 microns to 50 microns. Crushing / grinding can be completed in a ball mill, a continuous Egger grinder or any other similar equipment. The slurry generally has a pH of 2 to less than 9, and if necessary, can be adjusted by adding inorganic or organic acids and / or alkalis. The solid content of the slurry can be, for example, 15% to 60% by weight. When a pore-forming agent is used, it can be incorporated into the slurry at any time during the slurry preparation, for example, before crushing / grinding.

[0091] The resulting slurry can be applied to a substrate by dipping the substrate into the slurry, or otherwise coating the substrate, so that the desired loading of coating will be deposited on the substrate. Thereafter, the coated substrate can be dried at a temperature in the range of 100°C to 300°C and / or calcined by heating at a temperature in the range of 350°C to 650°C for a period of time, such as 1 hour to 3 hours. Drying and calcining are typically performed in air. If necessary, the coating process, drying process, and calcining process can be repeated to achieve the final desired weight amount of the catalyst washcoat on the carrier. The catalyst washcoat loading can be determined by calculating the difference in substrate weight before and after application of the washcoat.

[0092] The catalytic article according to the invention can be used to treat exhaust gas streams from automotive internal combustion engines, especially gasoline engines. The catalytic article according to the invention can be particularly effective in treating exhaust gas streams from saddle-type vehicle engines. In particular, the catalytic article according to the invention is a TWC catalytic article.

[0093] Thus, in a third aspect of the invention there is provided an exhaust treatment system comprising a catalytic article as described herein, located downstream of a stoichiometric engine, particularly a gasoline engine. In some embodiments, the exhaust treatment system is particularly useful for saddle-type vehicle engines.

[0094] In a fourth aspect of the invention, there is provided a method for treating an exhaust gas stream, in particular an exhaust gas stream from a stoichiometric engine, the method comprising contacting the exhaust gas stream with a catalytic article or an exhaust gas treatment system as described herein. In particular, the invention provides a method for treating an exhaust gas stream from a gasoline engine, preferably a saddle-type vehicle engine.

[0095] Implementation

[0096] Various embodiments are listed below. It should be understood that the embodiments listed below can be combined with all aspects of the scope of the present invention and other embodiments.

[0097] 1. A catalytic article comprising a catalyst coating on a substrate, wherein the catalyst coating comprises at least one catalyst coating, the at least one catalyst coating comprising a platinum group metal component in a supported form, and having a pore volume distribution such that, in a logarithmic differential pore volume distribution as determined by mercury intrusion porosimetry, the peak top of the nanometer-scale pore volume diameter exists in the range of 90.0 nm to 140.0 nm, and the peak top of the micrometer-scale pore volume diameter exists in the range of 5.5 μm to 140.0 nm.

[0098] 10.0μm range.

[0099] 2. The catalytic article according to embodiment 1, wherein the peak top of the nanoscale pore volume diameter exists in the range of 100.0 nm to 130.0 nm.

[0100] 3. The catalytic article according to embodiment 2, wherein the peak top of the nanoscale pore volume diameter exists in the range of 110.0 nm to 120.0 nm.

[0101] 4. The catalytic article according to any one of the preceding embodiments, wherein the peak top of the micrometer-sized pore volume diameter in the pore volume distribution exists in the range of 6.0 μm to 8.0 μm.

[0102] 5. The catalytic article according to embodiment 4, wherein the peak top of the micrometer-sized pore volume diameter in the pore volume distribution exists in the range of 6.0 μm to 7.5 μm.

[0103] 6. The catalytic article according to any one of the preceding embodiments, wherein the PGM component is a Pt component, a Pd component, a Rh component, or any combination thereof.

[0104] 7. The catalytic article according to any one of the preceding embodiments, wherein the catalyst coating comprises only one catalyst coating comprising a platinum group metal component in supported form.

[0105] 8. The catalytic article according to embodiment 7, wherein the catalyst coating consists of only one catalyst coating, and the only one catalyst coating comprises a platinum group metal component in supported form.

[0106] 9. The catalytic article according to any one of the preceding embodiments 1 to 6, wherein the catalyst coating comprises two catalyst coatings, the two catalyst coatings comprising a platinum group metal component in supported form.

[0107] 10. The catalytic article according to embodiment 9, wherein the catalyst coating consists of two catalyst coatings, and the two catalyst coatings contain a platinum group metal component in a supported form.

[0108] 11. The catalytic article of embodiment 9 or 10, wherein the catalyst coating comprises a top catalyst coating and a bottom coating, wherein the top catalyst coating comprises a first platinum group metal component in a supported form, and the bottom coating comprises a second platinum group metal component in a supported form.

[0109] 12. The catalytic article according to any one of embodiments 9 to 11, wherein the catalyst coating comprises two catalyst coatings, the two catalyst coatings comprising PGM components in a supported form, wherein one catalyst coating comprises a Rh component in a supported form and optionally a Pt component in a supported form as a PGM component, and the other catalyst coating comprises a Pt component in a supported form and optionally a Pd component in a supported form as a PGM component.

[0110] 13. A catalytic product according to embodiment 12, wherein the catalyst coating comprises a top catalyst coating and a bottom catalyst coating, wherein the top catalyst coating comprises a Rh component in a supported form and optionally a Pt component in a supported form as a PGM component, and the bottom catalyst coating comprises a Pt component in a supported form and optionally a Pd component in a supported form as a PGM component.

[0111] 14. A method for preparing a catalytic article according to any one of embodiments 1 to 8, the method comprising

[0112] - applying a slurry comprising a platinum group metal component in supported form and a pore former to a substrate, and optionally drying, and

[0113] - calcination to form a catalyst coating,

[0114] The pore former is in the form of particles, and is used in an amount of at least 0.5 wt % based on the loading of the catalyst coating as formed.

[0115] 15. A method for preparing a catalytic article according to any one of embodiments 1 to 6 and 9 to 13, the method comprising

[0116] - applying a slurry comprising a first platinum group metal component in supported form and a pore former to a substrate, and drying and / or calcining to form a first catalyst coating, and

[0117] - applying a slurry comprising a second platinum group metal component in supported form and a pore former onto the first catalyst coating, and optionally drying, and calcining to form a second catalyst coating,

[0118] The pore former is in the form of particles, and is used in an amount of at least 0.5 wt % based on the loading of each catalyst coating layer as formed.

[0119] 16. The method according to embodiment 14 or 15, wherein the pore former is used in an amount of at least 1 wt % based on the loading of each catalyst coating as formed.

[0120] 17. The method according to embodiment 16, wherein the pore former is used in an amount of at least 3 wt%.

[0121] 18. The method according to embodiment 17, wherein the pore former is used in an amount of at least 4 wt%.

[0122] 19. The method according to any one of embodiments 14 to 18, wherein the pore former is used in an amount of 50 wt% or less based on the loading amount of each catalyst coating layer as formed.

[0123] 20. The method according to embodiment 19, wherein the pore former is used in an amount of 30 wt% or less.

[0124] 21. A method according to any one of embodiments 14 to 20, wherein the pore former is selected from organic materials such as natural and synthetic polymers, organic solid small molecule compounds, inorganic materials such as inorganic salts and carbon materials, cellulose-containing natural materials, and any combination thereof.

[0125] 22. The method according to embodiment 21, wherein the pore former is selected from polyether polyols,

[0126] Such as polyethylene glycol and its alkyl-terminated derivatives, styrene homopolymers or copolymers,

[0127] Such as polystyrene, poly(meth)acrylic acid and their ester derivatives, such as polymethyl methacrylate or cross-linked polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, and any combination thereof.

[0128] 23. The method according to any one of embodiments 14 to 22, wherein the pore former is in the form of a powder, the pore former having an average particle size in the range of 1 μm to 50 μm

[0129] D 50 .

[0130] 24. The method according to embodiment 23, wherein the average particle size D 50 In 10μm to

[0131] Within the range of 30μm.

[0132] 25. The method according to embodiment 24, wherein the average particle size D 50 In the range of 15μm to 20μm.

[0133] 26. An exhaust gas treatment system, comprising the exhaust gas treatment system according to embodiments 1 to 13

[0134] The catalytic article of any one of claims 1 to 6, wherein the catalytic article is located downstream of a stoichiometric engine.

[0135] 27. An exhaust gas treatment system according to embodiment 26, wherein the stoichiometric engine is a gasoline engine, in particular a saddle-type vehicle engine.

[0136] 28. A method for treating an exhaust flow, particularly an exhaust flow from a stoichiometric engine, the method comprising contacting the exhaust flow with a catalytic article according to any one of embodiments 1 to 13 or an exhaust treatment system according to embodiment 26 or 27.

[0137] 29. The method of embodiment 28, wherein the exhaust gas stream is from a gasoline engine,

[0138] Preferably it is a saddle-riding vehicle engine.

[0139] Example

[0140] Various aspects of the present invention will be more fully described by the following examples, which are set forth for the purpose of illustrating certain aspects of the present invention and should not be construed as limiting the present invention.

[0141] Preparation of catalytic products

[0142] Example 1 (Sample S1, Comparative Example)

[0143] 1.56 g of aqueous hexahydroxyplatinate diethanolamine ((MEA)2Pt(OH)6) (16 wt% Pt) was diluted in water and loaded by incipient wetness onto a support consisting of 28.83 g of ceria-doped alumina (10% CeO2) and 163.37 g of ceria-zirconia (45% CeO2). The solid content after incipient wetness was 68 wt%. The obtained mixture was then mixed with an aqueous solution of 0.6 g of 1-octanol, 4.82 g of barium acetate, 2.1 g of zirconium acetate, 2.0 g of acetic acid and 2.0 g of alumina to provide a slurry having a solid content of 45%. The slurry was then ground until the resulting particle size D 90 The obtained slurry (hereinafter referred to as slurry A) had a final pH of 4.5 and a solid content of 41 wt%.

[0144] 6.42 g of aqueous neodymium nitrate (Nd(NO3)3) (29.8 wt% Nd) and 3.24 g of aqueous rhodium nitrate (Rh(NO3)3) (10 wt% Rh) were diluted in water and loaded sequentially by incipient wetness onto a support consisting of 97.64 g of lanthanum-doped zirconium oxide (9 wt% La2O3) and 49.33 g of cerium oxide-zirconia (10 wt% CeO2). The solid content after incipient wetness was 67 wt%. The obtained mixture was then mixed with an aqueous solution of 0.6 g of 1-octanol, 4 g of barium acetate and 45 g of aluminum oxide to provide a slurry having a solid content of 33 wt%. The slurry was then ground until the resulting particle size D 90 The slurry was 45 microns and then adjusted with nitric acid to a final pH of 4.5. The solid content of the obtained slurry (hereinafter referred to as slurry B) was 30% by weight.

[0145] A metal flow-through substrate with a diameter of 40 mm and a length of 90 mm having channels with a sinusoidal cross-sectional shape, 300 holes per square inch and a wall thickness of 5 mils was used as the substrate. Slurries A and B were then sequentially applied over the entire length of the substrate. The substrate was dried at 110° C. to remove between 85% and 95% of the moisture and then calcined at 550° C. for 2 hours after each coating. The loadings of the bottom coating obtained from slurry A and the top coating obtained from slurry B were 2.08 g / in 3 and 1.25g / in 3 The bottom coating contains 4.5g / ft 3 Pt, and the top coating contains 3.5g / ft 3 Rh.

[0146] Example 2 (Sample S2 of the present invention)

[0147] The preparation was the same as that of Example 1, except that 0.104 g / in 3 and 0.066 g / in 3 Cross-linked polymethyl methacrylate (PMMA, SUNPMMA-S200 from SUNJIN Chemical, polydisperse, D 50 =17 microns, D 100 =36.24 μm).

[0148] Example 3 (Sample S3 of the present invention)

[0149] The preparation was the same as that of Example 2, except that 0.208 g / in 3 and 0.132 g / in 3 of PMMA.

[0150] Example 4 (Sample S4, Comparative Example)

[0151] The preparation was the same as that of Example 2, except that 0.416 g / in 3 and 0.264 g / in 3 of PMMA.

[0152] Example 5 (Sample S5, Comparative Example)

[0153] 0.119 g of aqueous hexahydroxyplatinate diethanolamine (12 wt % Pt) was diluted in water and loaded by initial wetness onto a support consisting of 41.81 g of ceria-doped alumina (10 wt % CeO2) and 150.52 g of ceria-zirconia (45 wt % CeO2). The solid content after initial wetness was 68 wt %. The obtained mixture was then mixed with an aqueous solution of 0.7 g of 1-octanol, 6.99 g of barium acetate, 6.0 g of nitric acid and 3.3 g of alumina to provide a slurry with a solid content of 45 wt %. The slurry was then ground until the resulting particle size D 90 The obtained slurry (hereinafter referred to as slurry C) had a final pH of 4.5 and a solid content of 41 wt%.

[0154] 12.24 g of an aqueous lanthanum nitrate solution (27 wt% La) and 2.335 g of an aqueous palladium nitrate solution (21 wt%) were diluted in water and sequentially loaded by initial wetness onto a support consisting of 95.48 g of lanthanum-doped alumina (1 wt% La2O3) to obtain a mixture having a solid content of 55 wt% after initial wetness. 0.144 g of aqueous neodymium nitrate (30 wt% Nd) and 2.465 g of aqueous rhodium nitrate (10 wt% Rh) were diluted in water and sequentially loaded by initial wetness onto a support consisting of 10.61 g of zirconia-doped alumina (20 wt% ZrO2) and 37.13 g of cerium oxide-zirconia (22 wt% CeO2) to obtain a mixture having a solid content of 66 wt% after initial wetness. 1.53 g of aqueous hexahydroxyplatinate diethanolamine (12 wt % Pt) was diluted into water and loaded onto a support of 42.44 g of ceria-doped alumina (10 wt % CeO2) by initial wetness to obtain a mixture having a solid content of 60 wt % after initial wetness. The above mixture was then mixed in an aqueous solution of 0.7 g of 1-octanol, 3.0 g of nitric acid, 2.55 g of barium sulfate and 4.24 g of alumina to provide a slurry having a solid content of 33 wt %. The slurry was then ground until the resulting particle size D 90 The obtained slurry (hereinafter referred to as slurry D) had a final pH of 4 and a solid content of 31 wt%.

[0155] A metal flow-through substrate with a diameter of 40 mm and a length of 90 mm having channels with a sinusoidal cross-sectional shape, 300 holes per square inch and a wall thickness of 5 mils was used as the substrate. Slurries C and D were then sequentially applied over the entire length of the substrate. The substrate was dried at 120°C to remove between 85% and 95% of the moisture and then calcined at 550°C after each coating. The loadings of the bottom coating obtained from slurry C and the top coating from slurry D were 2.04 g / in 3and 0.96 g / in 3 The bottom coating contains 2.5g / ft 3 Pt, and the top coating contains 1.5g / ft 3 Pt, 4.0g / ft 3 Pd and 2.0g / ft 3 Rh.

[0156] Example 6 (Sample S6 of the present invention)

[0157] The preparation was the same as that of Example 5, except that 0.102 g / in 3 and 0.048 g / in 3 Cross-linked polymethyl methacrylate (PMMA, SUNPMMA-S200 from SUNJIN Chemical, polydisperse, D 50 =17 microns, D 100 =36.24 microns).

[0158] Example 7 (Sample S7 of the present invention)

[0159] The preparation was the same as that of Example 6, except that 0.204 g / in 3 and 0.096g / in 3 In addition to PMMA.

[0160] Example 8 (Sample S8 of the present invention)

[0161] The preparation was the same as that of Example 6, except that 0.408 g / in 3 and 0.192 g / in 3 In addition to PMMA.

[0162] Characterization of logarithmic differential pore volume distribution

[0163] The pore volume distribution in the catalyst coating of each catalyst preparation was examined by mercury intrusion (Poremaster 60). The measurements were performed on a standard mercury intrusion procedure using an automatic porosimeter "Poremaster 60" manufactured by Anton Paar Quanta Tec Inc. The samples for the measurements were prepared by scraping off a piece of the catalyst coating from each catalyst preparation.

[0164] Measurement temperature: 17.5℃;

[0165] Measuring hole: Sample chamber volume is 3cm 3 , and the intrusion volume is 0.39cm3 ;

[0166] Measuring range: 0.212PSIA to 59558.266PSIA;

[0167] Measurement points: 1071 points (when the aperture is applied logarithmically, the points are engraved at equal intervals).

[0168] The characterization results of the pore volume distribution of each catalytic coating are summarized in Table 1 below and are also shown in Figures 1A to 2B middle.

[0169] Table 1

[0170]

[0171] Catalytic performance test

[0172] The test samples were prepared by aging the corresponding catalytic products prepared in the above examples in a fresh state or according to a standard bench cycle (SBC) at a temperature of 820°C to 940°C and a lambda value of 0.9 to 1.1 for 18 hours, and loading them into a housing having an inlet and an outlet for passing the gas stream to be treated. The test samples were respectively equipped on a 125cc Wuyang-Honda motorcycle (WH125T-9A) or a 125cc Dachangjiang motorcycle (DCJ-HJ125T-22A).

[0173] Measurement of emissions

[0174] According to GB14622-2016, Type I, the World Motorcycle Test Cycle (WMTC) is used to measure each pollutant (THC, CO and NO x ) emissions.

[0175] By measuring tailpipe total hydrocarbons (THC), CO and NO x The performance of each test sample is evaluated by emissions from the following two phases included in one test cycle:

[0176] P1: Cold start phase from 0 seconds to 600 seconds,

[0177] P2: Hot phase from 600 to 1200 seconds.

[0178] At a fuel consumption of 2.17 L / 100 km, the exhaust gas from the two phases has the following cumulative composition:

[0179] P1: 2.200g / km CO, 0.499g / km THC, 0.440g / km NO x ,

[0180] P2: 1.660g / km CO; 0.389g / km THC; 0.493g / km NO x .

[0181] Each sample was tested three times to obtain an average value thereof as the test result. The test results of the emissions are summarized in Tables 2 to 5 below.

[0182] Table 2 THC, CO, and NO of 125cc motorcycle WH125T-9A and aged samples S1 to S4 x Emissions

[0183]

[0184] * The percentage of emission reduction compared to sample S1

[0185] Table 3 THC, CO, and NO of 125cc motorcycle DCJ-HJ125T-22A and aged samples S1 to S4 x Emissions

[0186]

[0187] * The percentage of emission reduction compared to sample S1

[0188] From the test results shown in Tables 2 and 3, it can be seen that the catalytic articles (S2 and S3) comprising a catalyst coating having a pore volume distribution as described herein according to the present invention show a significantly lower catalytic activity against HC, CO and NO than the catalytic articles (S1 and S4) comprising a catalyst coating not having a pore volume distribution as described herein. x Overall improved control of emissions.

[0189] Table 4 THC, CO, and NO in 125cc motorcycle WH125T-9A and fresh samples S5 to S8 x Emissions

[0190]

[0191]

[0192] * The percentage of emission reduction compared with sample S5

[0193] Table 5 THC, CO, and NO in 125cc motorcycle DCJ-HJ125T-22A and fresh samples S5 to S8 x Emissions

[0194]

[0195] * The percentage of emission reduction compared with sample S5

[0196] In addition, from the test results shown in Tables 4 and 5, it can be seen that the catalytic articles (S6 to S8) comprising the catalyst coating having the pore volume distribution as described herein according to the present invention show improved catalytic performance against HC, CO and NO compared to the catalytic article (S5) comprising the catalyst coating not having the pore volume distribution as described herein. xOverall improved control of emissions.

[0197] Although the present invention has been described herein with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and variations may be made to the methods and apparatus of the present invention without departing from the spirit and scope of the present invention. Therefore, the present invention is intended to include modifications and variations within the scope of the appended claims and their equivalents.

Claims

1. A catalytic article comprising a catalyst coating on a substrate, wherein the catalyst coating comprises at least one catalyst coating, the at least one catalyst coating comprising a platinum group metal component in a supported form and having a pore volume distribution such that, in a logarithmic differential pore volume distribution as determined by mercury intrusion porosimetry, the peak top of the nanometer-scale pore volume diameter exists in the range of 90.0 nm to 140.0 nm, and the peak top of the micrometer-scale pore volume diameter exists in the range of 5.5 μm to 10.0 μm.

2. The catalytic article according to claim 1, wherein the peak top of the nanoscale pore volume diameter exists in the range of 100.0 nm to 130.0 nm, or 110.0 nm to 120.0 nm.

3. The catalytic article according to claim 1 or 2, wherein the peak top of the micrometer-sized pore volume diameter in the pore volume distribution exists in the range of 6.0 μm to 8.0 μm, or 6.0 μm to 7.5 μm.

4. The catalytic article according to any one of claims 1 to 3, wherein the PGM component is a Pt component, a Pd component, a Rh component, or any combination thereof.

5. The catalytic article according to any one of claims 1 to 4, wherein the catalyst coating comprises or consists of only one catalyst coating comprising a platinum group metal component in supported form.

6. The catalytic article according to any one of claims 1 to 4, wherein the catalyst coating comprises or consists of two catalyst coatings comprising a platinum group metal component in supported form.

7. The catalytic article of claim 6, wherein the catalyst coating comprises or consists of a top catalyst coating comprising a first platinum group metal component in supported form and a bottom coating comprising a second platinum group metal component in supported form.

8. The catalytic article according to claim 6 or 7, wherein the catalyst coating comprises or consists of two catalyst coatings comprising PGM components in supported form, wherein one catalyst coating comprises a Rh component in supported form and optionally a Pt component in supported form as PGM components, and the other catalyst coating comprises a Pt component in supported form and optionally a Pd component in supported form as PGM components.

9. The catalytic article according to claim 8, wherein the catalyst coating comprises or consists of a top catalyst coating comprising a Rh component in a supported form and optionally a Pt component in a supported form as a PGM component, and a bottom catalyst coating comprising a Pt component in a supported form and optionally a Pd component in a supported form as a PGM component.

10. A method for preparing a catalytic article according to any one of claims 1 to 5, the method comprising - applying a slurry comprising a platinum group metal component in supported form and a pore former to a substrate, and optionally drying, and - calcination to form a catalyst coating, The pore former is in the form of particles, and is used in an amount of at least 0.5 wt % based on the loading of the catalyst coating as formed.

11. A method for preparing a catalytic article according to any one of claims 1 to 4 and 6 to 9, the method comprising - applying a slurry comprising a first platinum group metal component in supported form and a pore former to a substrate, and drying and / or calcining to form a first catalyst coating, and - applying a slurry comprising a second platinum group metal component in supported form and a pore former onto the first catalyst coating, and optionally drying, and calcining to form a second catalyst coating, The pore former is in the form of particles, and is used in an amount of at least 0.5 wt % based on the loading of each catalyst coating layer as formed.

12. The method according to claim 10 or 11, wherein the pore former is used in an amount of at least 1 wt%, at least 3 wt% or at least 4 wt% based on the loading of each catalyst coating as formed.

13. The method according to any one of claims 10 to 12, wherein the pore former is used in an amount of 50 wt% or less, or 30 wt% or less, based on the loading of each catalyst coating layer as formed.

14. The method according to any one of claims 10 to 13, wherein the pore former is selected from organic materials such as natural and synthetic polymers, organic solid small molecule compounds, inorganic materials such as inorganic salts and carbon materials, cellulose-containing natural materials, and any combination thereof.

15. The method according to claim 14, wherein the pore former is selected from polyether polyols, such as polyethylene glycol and its alkyl-terminated derivatives, styrene homopolymers or copolymers, such as polystyrene, poly(meth)acrylic acid and their ester derivatives, such as polymethyl methacrylate or cross-linked polymethyl methacrylate, cellulose, ether and ester derivatives of cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, and any combination thereof.

16. The method according to any one of claims 10 to 15, wherein the pore former is in the form of a powder having an average particle size D in the range of 1 μm to 50 μm, or 10 μm to 30 μm, or 15 μm to 20 μm. 50 .

17. An exhaust gas treatment system comprising the catalytic article of any one of claims 1 to 9, the catalytic article being located downstream of a stoichiometric engine.

18. The exhaust gas treatment system of claim 17, wherein the stoichiometric engine is a gasoline engine, in particular, the stoichiometric engine is a saddle-type vehicle engine.

19. A method for treating an exhaust gas flow, in particular the exhaust gas flow from a stoichiometric engine, comprising contacting the exhaust gas flow with a catalytic article according to any one of claims 1 to 9 or an exhaust gas treatment system according to claim 17 or 18.

20. The method of claim 19, wherein the exhaust gas stream is from a gasoline engine, preferably the exhaust gas stream is from a saddle-type vehicle engine.

Citation Information

Patent Citations

  • Exhaust gas purifying catalyst

    US20170232425A1

  • Catalyst structure for treating exhaust gas

    WO2013118425A1

  • Catalyst structure for exhaust gas treatment

    WO2014156676A1

  • Exhaust gas purification catalyst

    WO2015037613A1